Recent advances in the characterization of genetically defined neurons that regulate internal‐state‐dependent taste modification in mice - Ken‐ichiro Nakajima (Physiological Reports)
Abstract The gustatory system plays an important role in evaluating food quality in animals and humans. While some tastes are intrinsically appetitive, such as sweet, which is elicited from high‐calorie nutrients, the other tastes, such as sour and bitter, are aversive and elicited by toxic substances. In mice, taste signals are relayed by multiple regions of the brain, including the nucleus of the solitary tract, and the parabrachial nucleus (PBN) of the pons, before reaching the gustatory cortex via the gustatory thalamus. Recent advances in taste research using mice expressing Cre recombinase in specific neuronal populations, together with chemogenetic/optogenetic tools, have enabled us to identify genetically defined neurons involved in taste transduction pathways across several areas of the brain. While gustatory pathways play a fundamental role in taste transduction, taste preferences are not always stable, but rather vary depending on internal states. This review summarizes recent progress in research on neural circuits that modify the taste information depending on internal states in mice.